1984
DOI: 10.1111/j.1399-0004.1984.tb01105.x
|View full text |Cite
|
Sign up to set email alerts
|

New anomalies found in the 11q‐ syndrome

Abstract: The cytogenetic analysis of an infant with multiple congenital anomalies revealed a small deletion of the long arm of one No. 11 chromosome: 46XX del 11 (q23‐q25). The main clinical manifestations included: trigonocephaly, flat broad nasal bridge, micrognathia, carp mouth, hypertelorism, low set ears, severe congenital heart disease, anomalies of limbs and external genitalia. In comparison to the previously reported cases of 1 lq‐, the patient presented here had congenital anomalies not described before, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The most frequent breakpoint observed in 1 Iq deletion syndrome is located at band llq23 (Engel et al 1976, Larson et al 1976, Bresson & Noir 1977, Cassidy et al 1977, Frank & Riccardi 1977, Kaffe et al 1977, Mulcahy & Jenkyn 1977, Schinzel et al 1977, Zabel et al 1977, Lkonard et al 1979, Lippe et al 1980, Ferry et al 1981, Lee & Sciorra 1981, McPherson & Meissner 1982, Monteleone et al 1982, Cousineau et al 1983, Sirota et al 1984. A breakpoint at llq23 was also found in partial distal l l q monosomies being the unbalanced product of familial translocations involving the long arm of chromosome 11 and another chromosome (Jacobsen et al 1973, Ridler & McKeown 1979, and also the same breakpoint is found in the classical 1 lq/22q translocation (Iselius et al 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent breakpoint observed in 1 Iq deletion syndrome is located at band llq23 (Engel et al 1976, Larson et al 1976, Bresson & Noir 1977, Cassidy et al 1977, Frank & Riccardi 1977, Kaffe et al 1977, Mulcahy & Jenkyn 1977, Schinzel et al 1977, Zabel et al 1977, Lkonard et al 1979, Lippe et al 1980, Ferry et al 1981, Lee & Sciorra 1981, McPherson & Meissner 1982, Monteleone et al 1982, Cousineau et al 1983, Sirota et al 1984. A breakpoint at llq23 was also found in partial distal l l q monosomies being the unbalanced product of familial translocations involving the long arm of chromosome 11 and another chromosome (Jacobsen et al 1973, Ridler & McKeown 1979, and also the same breakpoint is found in the classical 1 lq/22q translocation (Iselius et al 1983).…”
Section: Discussionmentioning
confidence: 99%
“…They were most frequently occurring de novo (Linarelli et al 1975, Turleau et al 1975, Engel et al 1976, Larson et al 1976, Bresson & Noir 1977, Cassidy et al 1977Frank & Riccardi 1977, Kaffe et al 1977, Mulcahy & Jenkyn 1977, Zabel et al 1977, Felding & Mitelman 1979, Laurent et al 1979, Leonard et al 1979, Lippe et al 1980, Ferry et al 198 1, Lee & Sciorra 198 1, McPherson & Meissner 1982, Monteleone et al 1982, Cousineau et a]. 1983, O'Hare et al 1984, Sirota et al 1984. A smaller number resulted from familial or de novo translocations (Fonatsch et al 1975, Coco & Penchaszadeh 1977, Ridler & Mc-Keown 1979, Grosse et al 1981.…”
mentioning
confidence: 99%
“…The other patients presented with platelet counts of more than lOOX 103/mm3. nasal bridge, upturned nose, thin lips, congenital heart disease, mental retardation (O'Hare et al 1984, Fryns et al 1986, Schwarz et al 1992, Sirota et al 1984).…”
mentioning
confidence: 99%
“…Using molecular breakpoint mapping in patients with a terminal 11q deletion previously identified by karyotype analysis, Grossfeld et al 2004 have not identified any interstitial deletion. To the best of our knowledge, only 15 patients with de novo interstitial deletions have been published thus far [Taillemite et al, 1975; Sorensen et al, 1979; McPherson and Meissner, 1982; Sirota et al, 1984; Klep‐de Pater et al, 1985; Carnevale et al, 1987; Guc‐Scekic et al, 1989; Wakazono et al, 1992; Stratton et al, 1994; Ono et al, 1996; Pivnick et al, 1996; De Pater et al, 1997; Wenger et al, 2006]. The size and breakpoints of the deletions are highly variable (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…In most patients, terminal deletions are observed with cytogenetic breakpoints in 11q23 or 11q24 [Penny et al, 1995; Grossfeld et al, 2004]. Only a few interstitial deletions have been reported to date, extending from the proximal long arm (11q13) to one of the distal cytogenetic bands (up to 11q25) [Taillemite et al, 1975; Sorensen et al, 1979; McPherson and Meissner, 1982; Sirota et al, 1984; Klep‐de Pater et al, 1985; Carnevale et al, 1987; Guc‐Scekic et al, 1989; Wakazono et al, 1992; Stratton et al, 1994; Ono et al, 1996; Pivnick et al, 1996; De Pater et al, 1997; Wenger et al, 2006]. Additionally, patients have been described with deletions resulting from familial balanced translocations or inversions [Pivnick et al, 1996; Zahn et al, 2005; Gadzicki et al, 2006], de novo unbalanced translocations [Van Hemel et al, 1992; Penny et al, 1995; Wenger et al, 2006; Courtens et al, 2007], and ring chromosomes [Pivnick et al, 1996].…”
Section: Introductionmentioning
confidence: 99%